Long COVID: An inevitable sequela of SARS-CoV-2 infection - Lai, Chih-Cheng; Hsu, Chi-Kuei; Yen, Muh-Yong; Lee, Ping-Ing; Ko, Wen-Chien; Hsueh, Po-Ren (Journal of microbiology, immunology and infection, 2023)
At present, there are more than 560 million confirmed cases of the coronavirus disease 2019 (COVID-19) worldwide. Although more than 98% of patients with severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection can survive acute COVID, a significant portion of survivors can develop residual health problems, which is termed as long COVID. Although severe COVID-19 is generally associated with a high risk of long COVID, patients with asymptomatic or mild disease can also show long COVID. The definition of long COVID is inconsistent and its clinical manifestations are protean. In addition to general symptoms, such as fatigue, long COVID can affect many organ systems, including the respiratory, neurological, psychosocial, cardiovascular, gastrointestinal, and metabolic systems. Moreover, patients with long COVID may experience exercise intolerance and impaired daily function and quality of life. Long COVID may be caused by SARS-CoV-2 direct injury or its associated immune/inflammatory response. Assessment of patients with long COVID requires comprehensive evaluation, including history taking, physical examination, laboratory tests, radiography, and functional tests. However, there is no known effective treatment for long COVID. Based on the limited evidence, vaccines may help to prevent the development of long COVID. As long COVID is a new clinical entity that is constantly evolving, there are still many unknowns, and further investigation is warranted to enhance our understanding of this disease.